The impact of the disability support pension on mental health: evidence from 14 years of an Australian cohort - Allison Milner; Anne Kavanagh; Ashley McAllister; Zoe Aitken (Elsevier, 2020)
Abstract Objective: To assess the effect of the Australian Disability Support Pension (DSP) on the symptomology of depression and anxiety over and above the effects of reporting a disability itself. Methods: We used the Household Income Labour Dynamics in Australia (HILDA) survey from 2004 to 2017. We used fixed effects regression to understand mental health differences (using the Mental Health Inventory‐5 [MHI‐5]) when a person reported: i) a disability; or ii) a disability and receiving the DSP) compared to when they reported no disability. The models controlled for time‐varying changes in the severity of the disability and other time‐related confounders. Results: There was a 2.97‐point decline (95%CI −3.26 to −2.68) in the MHI‐5 when a person reported a disability compared to waves in which they reported no disability and 4.48‐point decline (95%CI −5.75 to −3.22) when a person reported both a disability and being on the DSP compared to waves in which they reported neither. Conclusions: Results suggest that accessing and being in receipt of the DSP can impact the mental health of people with disabilities. Implications for public health: Government income support policies should address the unintended adverse consequences in already vulnerable populations.